Roles of the “Dispensable” Portions of RAG-1 and RAG-2 in V(D)J Recombination - Steen, S. B. (American Society for Microbiology, 1999)
V(D)J recombination is initiated by introduction of site-specific double-stranded DNA breaks by the RAG-1 and RAG-2 proteins. The broken DNA ends are then joined by the cellular double-strand break repair machinery. Previous work has shown that truncated (core) versions of the RAG proteins can catalyze V(D)J recombination, although less efficiently than their full-length counterparts. It is not known whether truncating RAG-1 and/or RAG-2 affects the cleavage step or the joining step of recombination. Here we examine the effects of truncated RAG proteins on recombination intermediates and products. We found that while truncated RAG proteins generate lower levels of recombination products than their full-length counterparts, they consistently generate 10-fold higher levels of one class of recombination intermediates, termed signal ends. Our results suggest that this increase in signal ends does not result from increased cleavage, since levels of the corresponding intermediates, coding ends, are not elevated. Thus, removal of the “dispensable” regions of the RAG proteins impairs proper processing of recombination intermediates. Furthermore, we found that removal of portions of the dispensable regions of RAG-1 and RAG-2 affects the efficiency of product formation without altering the levels of recombination intermediates. Thus, these evolutionarily conserved sequences play multiple, important roles in V(D)J recombination.